The Influence of Opinion Shopping, Audit Quality, and Financial Condition on Going Concern Audit Opinions : A Study on Construction and Infrastructure Sector Companies Listed on the Indonesia Stock Exchange in 2021–2023 - Wahyoeni, Sri Irviati; Putri, Mellyana; Biandani, Tryas Chas (Golden Ratio of Auditing Research, 2025)
This study aims to determine the effect of opinion shopping, audit quality, and financial condition proxied by the debt-to-equity ratio on going concern audit opinions. The dependent variable used is in the form of a dummy. This research uses quantitative research methods. The sample in this study was selected using a purposive sampling technique, which obtained 37 construction and infrastructure sector companies listed on the Indonesia Stock Exchange in 2021-2023, with a total sample of 111. Data collection techniques in this study used documentation techniques and library research. The data collected is the company's financial reports and annual reports. The data analysis technique used was logistic regression analysis with SPSS version 30. The results showed that opinion shopping affected the going concern audit opinion, while audit quality and financial condition did not affect the going concern audit opinion.